Implementation and Benefits of Digital Accounting for the Development of Creative Industry MSMEs in Surakarta City (International Journal of Economics and Management Research, 2026)
This study aims to analyze the effect of digital accounting implementation on the development of micro, small, and medium enterprises (MSMEs) in the creative industry sector in Surakarta City. A quantitative approach with a cross-sectional survey design was employed. Data were collected through a closed-ended questionnaire administered to 120 MSME actors who had implemented digital accounting applications, and were analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method. The findings indicate that digital accounting implementation has a significant effect on MSME development. The use of digital accounting systems has been proven to improve the efficiency of financial recording, support data-driven decision-making, and enhance both managerial capacity and market expansion. The path coefficient shows a strong positive relationship between the two variables, with a contribution of 46.8% to the variance in MSME development. These findings highlight the importance of digitalization in MSME financial governance, particularly in the innovation-driven and dynamic creative industry sector. Digital accounting serves not only as an administrative tool but also as a strategic instrument to strengthen business competitiveness and sustainability. Therefore, synergy among business actors, local government, and technology providers must be strengthened to create an inclusive and sustainable digital ecosystem.